A review of how psychotropic medication can affect the motivation of challenging behavior. (2nd July 2016) - Cox, Alison D.; Virués-Ortega, Javier
Abstract : Self-injury, aggression, stereotypy, and other forms of challenging behavior are highly prevalent among people with intellectual disabilities (ID). Psychopharmacological and behavioral interventions, often in combination, are common interventions for challenging behavior. However, little is known about the interaction between psychopharmacological treatment and the motivation or, more precisely, the function of challenging behavior. A better understanding of these processes may be critical to optimize treatment efficacy. Objectives : An overall review of the literature on the interaction between behavior function and psychotropic medication in people with ID, and directly related variables (e.g. motivating operations) was conducted. As a result, we discuss the behavioral processes involved in medication–behavior function interaction and the methodological and clinical implications of this research area. Methods : A comprehensive literature review was conducted of current peer-reviewed publications. Results and Conclusion : Evidence suggests medication can affect the function of challenging behavior in several ways (i.e. add new functions, decrease the number of functions, and/or change the function). Moreover, medication–function interaction was a relatively infrequent occurrence. We found the analysis of variables that alter the effectiveness of a reinforcing or punishing stimulus, called motivating operations (e.g. satiation, deprivation, illness) provides an experimental model for the analysis of the behavioral mechanisms associated with medication–function interactions. Further, single-subject designs and functional analysis methodology can be combined to evaluate medication–function interactions.